On the role of impurities on spheroidal graphite degeneracy in cast irons. (February 2021) - Domengès, Bernadette; Celis, Mayerling Martinez; Moisy, Florent; Lacaze, Jacques; Tonn, Babette
Abstract: Though manufacturing spheroidal graphite cast irons is a well-established industrial process, good nodularity which is essential for mechanical properties may be hampered by several factors. Amongst them is the presence of impurities at trace level which lead to the growth of protrusions and the question is how they can destroy the spheroidizing effect of magnesium. For the first time, it is shown that such impurities are present together with magnesium at the interface between spheroid and protrusion. For getting this result, site-specific electron transparent lamellae were prepared using Focused Ion Beam and characterized at nanometric scale using atomic resolution scanning-transmission electron microscope. It is also shown by automatic crystal orientation mapping that there is no definite crystallographic relationship between protrusions and underlying spheroids. Graphical abstract: Image 1 Highlights: The rising question is how trace elements (impurities) can destroy the spheroidizing effect of magnesium in cast irons. Electron transparent lamellae were prepared by FIB and characterized at nanometric scale using Atomic Resolution TEM-STEM. It is shown that some impurities are present together with magnesium at the interface between spheroid and protrusion. A mechanism is proposed in which impurities adsorb preferentially to magnesium onto the prismatic planes of graphite. ACOM showed that there is no definite crystallographic relationship between protrusions and underlying spheroids.